2022
DOI: 10.1007/s40843-022-2277-9
|View full text |Cite
|
Sign up to set email alerts
|

面向高稳定性太阳能电池开发的卤化物钙钛矿稳定 性提升策略

Abstract: Perovskite is rising as the most promising material for the next generation of solar cells, due to its high efficiency, low cost, and convenient fabrication. However, the stability of perovskite solar cells remains to be a challenge towards large-scale application. Perovskite materials play a key role in improving the stability of PSCs, and tremendous efforts have been committed to stabilizing the perovskite materials, including composition regulation, crystallization control, and interface optimization. Herei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 72 publications
0
8
0
Order By: Relevance
“…where ε, ε 0 , L, V TFL , and e are perovskite relative permittivity, vacuum permittivity, perovskite-film thickness, limit voltage full of traps, and elementary charge, respectively. For the control and DADA-treated devices, the calculated electronand hole-trap densities were (4.10 and 3.12 × 10 16 ) and (2.30 and 1.90 × 10 15 ) cm −3 , respectively. Therefore, DADA substantially reduced both the electron-and hole-trap densities, which improved the PSC performance.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…where ε, ε 0 , L, V TFL , and e are perovskite relative permittivity, vacuum permittivity, perovskite-film thickness, limit voltage full of traps, and elementary charge, respectively. For the control and DADA-treated devices, the calculated electronand hole-trap densities were (4.10 and 3.12 × 10 16 ) and (2.30 and 1.90 × 10 15 ) cm −3 , respectively. Therefore, DADA substantially reduced both the electron-and hole-trap densities, which improved the PSC performance.…”
Section: Resultsmentioning
confidence: 99%
“…Because of their ionic properties, which are related to organic-cation and halide vacancies and uncoordinated lead and iodine ions, perovskites contain various defects, which are often mainly concentrated at grain boundaries and on perovskite surfaces. These defects capture charges, which generates nonradiative recombination and hysteresis and, thus, affects the device performance. In addition, defects promote ion migration and charge accumulation in the device, which destroys the device structure and considerably reduces both the device stability and performance. In the early development of PSCs, researchers mainly focused on the improvement of the perovskite active layer by engineering components, , optimizing fabrication processes, , engineering solvents, , and modifying interfaces by passivating defects to reduce the defect densities of perovskite active layers. Interfacial modification is a facile and effective method for reducing the number of surface defects.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 With respect to MHPs, they are sensitive to external stimulations such as moisture, heat, and oxygen. Over the last decade, tremendous efforts have been devoted to understanding the degradation mechanisms of MHPs and developing strategies for robust MHPs, 7 which have recently translated into impressive progress. 8 Ho-Baillie and Shi et al demonstrated that the outgassing of the organic component can be effectively suppressed by a polymer/glass stack pressure-tight encapsulation, enabling PSCs to pass both the damp heat test and humidity freezing test.…”
Section: Introductionmentioning
confidence: 99%
“…Tin perovskite solar cells are emerging as a promising thin-film photovoltaic technology due to the toxic-element-free character and superior optoelectronic properties, such as a desirable band gap with a high Shockley–Quisser limit efficiency (>33%) and excellent carrier mobility . Over the past few years, the power conversion efficiency (PCE) of tin perovskite solar cells increases rapidly from approximately 6% to over 14%. Significant efforts have been made to improve efficiency, including composition manipulation, dimensionality control, and the decrease of oxidation, , as well as device structural engineering. The use of a quasi-two-dimensional (quasi-2D) perovskite structure is an important approach to improve device performance since it can reduce oxidation and regulate film growth simultaneously …”
Section: Introductionmentioning
confidence: 99%